Observer-based H ∞ control for networked nonlinear systems with random packet losses - Li, Jian Guo; Yuan, Jing Qi; Lu, Jun Guo (ISA transactions, 2010)
This paper investigates the observer-based H ∞ control problem of networked nonlinear systems with global Lipschitz nonlinearities and random communication packet losses. The random packet loss is modelled as a Bernoulli distributed white sequence with a known conditional probability distribution. In the presence of random packet losses, sufficient conditions for the existence of an observer-based feedback controller are derived, such that the closed-loop networked nonlinear system is exponentially stable in the mean-square sense, and a prescribed H ∞ disturbance–rejection–attenuation performance is also achieved. Then a linear matrix inequality (LMI) approach for designing such an observer-based H ∞ controller is presented. Finally, a simulation example is used to demonstrate the effectiveness of the proposed method.